Fracture studies on bi-metallic pipe weld joints under monotonic and cyclic loading. (August 2021) - Vishnuvardhan, S.; Saravanan, M.; Gandhi, P.; Raghava, G.; Kumar, Suranjit; Khan, I.A.; Singh, P.K.
Abstract: Fracture studies were carried out on bi-metallic pipe weld joints of 324 mm outer diameter having crack at different regions of weld in the circumferential direction. The bi-metallic pipe weld joints were made of low alloy steel (ferritic) and stainless steel (austenitic) materials. Welding consumable used was nickel-based alloy. The initial notch was located in the different regions of the weld joints such as base metals (ferritic and austenitic), centre of weld, buttering (nickel-based alloy on low alloy steel) and heat affected zones. Subsequent to fatigue pre-cracking, fracture tests were carried out under four-point bending under monotonic and cyclic loading. During the fracture tests, load, load-line displacement, deflections, circumferential deformations, surface crack growth, crack mouth opening displacement were recorded. In addition, number of cycles to failure were monitored for tests under cyclic loading. Under monotonic loading, collapse load of the bi-metallic pipe weld joint having initial crack in the centre of buttering reduced by 12% in comparison to the collapse load for crack in the centre of heat affected zone. Crack deviated towards austenitic region for the weld joints having crack in the centre of weld, centre of buttering and heat affected zone. The bi-metallic pipe weld joints subjected to cyclic loading failed at lower number of cycles even when the load amplitude was sufficiently below the collapse load under monotonic loading. Crack growth resistance of bimetallic pipe weld joints under cyclic loading was significantly lower compared to that under monotonic loading under displacement control. Graphical abstract: Image 1 Highlights: Fracture studies were carried out on bi-metallic pipe weld joints under monotonic and cyclic loading. Initial crack in the buttering layer reduced the collapse load by 12% when compared with initial crack in HAZ. Irrespective of the location of initial crack in the weld, HAZ or buttering, crack growth was in the austenitic region. Crack growth resistance under cyclic loading was significantly lower compared to that under monotonic loading.